The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/chem.201803508
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Catalysis: Hydroboration of Aldehydes Using a Benzo‐Fused Diaza‐benzyloxy‐arsole

Abstract: The first example of a homogenous As catalyst for hydroboration has been established. The reaction of N,N'-diisopropylbenzene diamine or toluene-3,4-dithiol with AsCl yielded the chloroarsoles (1 and 2), which upon reaction with benzyl alcohol yielded the benzyloxy benzo-1,3,2-diazaarsole (3) and benzo-1,3,2-dithiaarsole (4), respectively. Compound 3 was found to be an excellent catalyst for the hydroboration of aldehyde substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
(29 reference statements)
2
25
0
Order By: Relevance
“…It was found that bis(amino) ligands were necessary to isolate stable crystalline ions, as previously observed by Arduengo with imidazol‐2‐ylidenes . Related silyene, germylene, phosphenium and arsenium ions have also been reported . In 2011, Gandelman demonstrated that nitrenium cations can serve as ambiphilic ligands on rhodium and that they behave as weak σ‐donors but considerable π‐acceptors .…”
Section: Figurementioning
confidence: 57%
See 1 more Smart Citation
“…It was found that bis(amino) ligands were necessary to isolate stable crystalline ions, as previously observed by Arduengo with imidazol‐2‐ylidenes . Related silyene, germylene, phosphenium and arsenium ions have also been reported . In 2011, Gandelman demonstrated that nitrenium cations can serve as ambiphilic ligands on rhodium and that they behave as weak σ‐donors but considerable π‐acceptors .…”
Section: Figurementioning
confidence: 57%
“…Over the last decade there has been increasing interest in studying pnictogens, often considered Lewis basic given the availability of an energetically accessible lone pair, in this unconventional role. This work has been expanded to include compounds of phosphorus, arsenic, antimony, and bismuth . By contrast, the reactivity of nitrogen‐containing compounds as Lewis acids has been investigated to a much lesser extent, largely due to the dearth of such species.…”
Section: Figurementioning
confidence: 99%
“…Traditional examples of main-group Lewis acid catalysts involve group 13 and 14 elements as the central locus of reactivity,a stheyf eature al ow-lying orbital for substrate activation. [1] Over the last decade there has been increasing interest in studying pnictogens,o ften considered Lewis basic given the availability of an energetically accessible lone pair, in this unconventional role.T his work has been expanded to include compounds of phosphorus, [2][3][4][5][6][7][8][9][10][11] arsenic, [12] antimony, [13][14][15][16][17][18][19][20] and bismuth. [21][22][23] By contrast, the reactivity of nitrogen-containing compounds as Lewis acids has been investigated to am uch lesser extent, largely due to the dearth of such species.C hloramines,n itrenes,d iazocarboxylates,azides,and diazonium salts have been shown to possess N-centered electrophilic behavior.…”
Section: Nitrenium Salts In Lewis Acid Catalysismentioning
confidence: 99%
“…[30] Related silyene,germylene,phosphenium and arsenium ions have also been reported. [12,[31][32][33][34] In 2011, Gandelman demonstrated that nitrenium cations can serve as ambiphilic ligands on rhodium and that they behave as weak s-donors but considerable pacceptors. [35] Stoichiometric investigations of these ions with Lewis bases were also undertaken by Gandelman, demonstrating that the Lewis acidic centre is primarily located on the internal nitrogen ( Figure 1).…”
Section: Nitrenium Salts In Lewis Acid Catalysismentioning
confidence: 99%
“…However, toxic metal salts involving As, Pb, Hg, Cd, etc. still being used as the homogeneous catalysts for the specific organic transformations . Only a few reports are available for the use of these sorbents in achieving the dual objective of remediation and catalysis applications …”
Section: Introductionmentioning
confidence: 99%